A survey of the views of US veterinary teaching faculty to owned cat housing practices. Issue 12 (December 2015) - Salo, Allen L; Stone, Elizabeth
According to the American Pet Products Association, in the USA there are an estimated 86.4 million owned cats, and approximately 40% of these are allowed to roam outdoors. Little has been written about the contribution of owned cats to problems attributed to feral cats, including wildlife predation, spread of zoonotic diseases and overpopulation. A recent study found that 64% of cats have visited the veterinarian within the past year, suggesting frequent opportunity for veterinarians to communicate risks and benefits of indoor vs outdoor living. We conducted the following survey to evaluate current views about this role of veterinarians, by surveying veterinary school faculty (n = 158). Our objectives were to assess (i) the degree to which veterinary teaching faculty believe that the issue of clients maintaining owned cats indoors vs outdoors is appropriate for discussion with students within the veterinary school curriculum; (ii) the degree of agreement and understanding there is among the faculty as to the reasons that clients maintain cats either inside or outside the home; and (iii) the degree to which veterinary faculty believe owned cats that are allowed to go outdoors contribute to various identified problems. The results indicated that many participants believed that the discussion of maintaining cats indoors is relevant to the profession, that it belongs in the veterinary school curriculum, that they understand client motivations, that they feel that more practicing veterinarians should discuss cat housing practices with clients and that cat overpopulation continues to be a significant concern for owned cats being outdoors. Additional ways to help maintain the health and wellbeing of cats that are primarily housed indoors is briefly discussed, including through such means as environmental enrichment or by providing cats access to safe areas while outdoors.